Representation Moral Values in the Serial “Alrawabi School For Girls” by Tima Shomali and Shirin Kamal: A Sociological Literature Study - Ningrum, Wilda; Abdul Halim, Muhamad; Khomisah, Khomisah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
In contemporary media, series reflect societal values, including moral principles in human interactions. Some modern series present moral dilemmas that challenge traditional ethical norms. AlRawabi School for Girls explores bullying, revenge, and justice, raising concerns about its impact on viewers' moral understanding. With the growing influence of media, it is essential to examine how moral values are portrayed in this series. This research aims to analyze the representation of moral values in the serial “Alrawabi School For Girls” by Tima Shomali And Shirin Kamal through a sociological literature approach. The study explores moral values related to human relationships with God, oneself, and others. The research employs a qualitative descriptive method, using textual analysis to identify moral messages embedded in dialogues and character interactions. Data collection is conducted through careful observation and note-taking of relevant excerpts, followed by an analysis within the framework of literary sociology. The primary data source consists of selected dialogues and scenes from the series that depict various moral values. The findings reveal that the series contains multiple moral values, including gratitude, honesty, courage, self-awareness, dignity, discipline, responsibility, friendship, empathy, care, justice, and solidarity.